Carlina vulgaris L. as a Source of Phytochemicals with Antioxidant Activity. (18th October 2017) - Strzemski, Maciej; Wójciak-Kosior, Magdalena; Sowa, Ireneusz; Załuski, Daniel; Szwerc, Wojciech; Sawicki, Jan; Kocjan, Ryszard; Feldo, Marcin; Dresler, Sławomir
Abstract : The methanol extracts from three populations of Carlina vulgaris L. were examined for the chlorogenic acid content, mineral content, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity. Two populations originated from natural nonmetallicolous habitats (NN (populations from Nasiłów) and NP (populations from Pińczów)), and one metallicolous population (MB) was collected from Bolesław waste heap localized at the place of former open-cast mining of Ag-Pb and Zn-Pb ores dating back to the 13th century and 18th century, respectively. The level of Zn, Pb, Cd, Fe, Ni, and Mn was significantly higher in the root and leaves of MB plants as a result of soil contaminations compared to those of the NN and NP ones. The highest antioxidant potency has been showed by the plants growing in a nonmetallicolous habitat. The flower head extracts obtained from the nonmetallicolous populations also contained the largest amount of chlorogenic acid, whereas the lowest was determined in the roots (ca. 2–3.5 mg/g and 0.2–0.4 mg/g of air-dry weight, resp.). These studies provide important information on the influence of a habitat on the quality of herbal materials and the content of the biologically active primary and secondary metabolites.